2023
DOI: 10.1371/journal.pone.0282627
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 vaccine tele-educational program on vaccine hesitancy and receiving the vaccine among women planning for pregnancy, pregnant or breast-feeding mothers

Abstract: Background COVID-19 hesitancy among women planning to become pregnant, who are pregnant, and who are breast-feeding is still a global phenomenon. Unfortunately, there is a lack of national educational programs that provide those groups of people with the information they need about the vaccine. Objective This study investigated the effect of the COVID-19 vaccine tele-educational program on vaccine hesitancy and receiving the vaccine among women planning for pregnancy, pregnant and breast-feeding mothers. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Three studies were conducted in Canada [ 31 , 36 , 51 ], two in Italy [ 38 , 41 ], and two in Taiwan [ 37 , 52 ]. The other seven studies occurred in Hong Kong [ 28 ], United Kingdom [ 39 ], France [ 47 ], India [ 46 ], Greece [ 40 ], Jordan [ 43 ], and Australia [ 45 ]. The majority of the studies (93%) were from high-income countries [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], and only two studies [ 43 , 46 ] were from low- and middle-income countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies were conducted in Canada [ 31 , 36 , 51 ], two in Italy [ 38 , 41 ], and two in Taiwan [ 37 , 52 ]. The other seven studies occurred in Hong Kong [ 28 ], United Kingdom [ 39 ], France [ 47 ], India [ 46 ], Greece [ 40 ], Jordan [ 43 ], and Australia [ 45 ]. The majority of the studies (93%) were from high-income countries [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], and only two studies [ 43 , 46 ] were from low- and middle-income countries.…”
Section: Resultsmentioning
confidence: 99%
“…The other seven studies occurred in Hong Kong [ 28 ], United Kingdom [ 39 ], France [ 47 ], India [ 46 ], Greece [ 40 ], Jordan [ 43 ], and Australia [ 45 ]. The majority of the studies (93%) were from high-income countries [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], and only two studies [ 43 , 46 ] were from low- and middle-income countries. In total, fourteen studies focused on the influenza vaccine [ 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 39 , 40 , 41 , 46 ], six studies on Tdap vaccine [ …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 Other studies on the effects of vaccine hesitancy on women showed that pregnant women’s awareness of the COVID-19 vaccination after receiving a tele-education session about it reduced their hesitation and increased their willingness to receive the vaccination. 8 In this study, respondents who agreed to the vaccine were motivated by the risk of morbidity and possible risk of death. These results were supported by findings from several other studies that focused on willingness to be vaccinated against COVID-19.…”
Section: Introductionmentioning
confidence: 99%